2013
DOI: 10.1128/jvi.00939-12
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Protein HAX1 Interacts with the Influenza A Virus PA Polymerase Subunit and Impedes Its Nuclear Translocation

Abstract: Transcription and replication of the influenza A virus RNA genome occur in the nucleus through the viral RNA-dependent RNA polymerase consisting of PB1, PB2, and PA. Cellular factors that associate with the viral polymerase complex play important roles in these processes. To look for cellular factors that could associate with influenza A virus PA protein, we have carried out a yeast two-hybrid screen using a HeLa cell cDNA library. We identified six cellular proteins that may interact with PA. We focused our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 78 publications
1
37
1
Order By: Relevance
“…In fact, from a recent genomic screening, only two factors that negatively modulate viral polymerase activity were found (75), and, furthermore, the physiological role of only a very few cases of influenza virus repressors has been characterized. Standing out among these are the characterization of Ebp-1, a suppressor of the androgenmediated transcription that inhibits RNA synthesis of the viral polymerase in vitro (76); cyclophilin E, which negatively regulates virus life cycle in infected cells (77); annexin 6, which impairs virus budding (78); and the HAX1 protein, which impedes the nuclear translocation of the PA polymerase subunit (79).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, from a recent genomic screening, only two factors that negatively modulate viral polymerase activity were found (75), and, furthermore, the physiological role of only a very few cases of influenza virus repressors has been characterized. Standing out among these are the characterization of Ebp-1, a suppressor of the androgenmediated transcription that inhibits RNA synthesis of the viral polymerase in vitro (76); cyclophilin E, which negatively regulates virus life cycle in infected cells (77); annexin 6, which impairs virus budding (78); and the HAX1 protein, which impedes the nuclear translocation of the PA polymerase subunit (79).…”
Section: Discussionmentioning
confidence: 99%
“…Optimal interactions of the polymerase complex with the host factors are required for the efficient viral replication and may determine the pathogenicity and host range of IAv. By functional assays, such as yeast two-hybrid screens, cell-free reconstitution systems or proteomics approaches, a number of cellular proteins have been identified as PAinteracting partners [117][118][119][120][121][122][123][124][125][126][127]. Bradel-Tretheway et al [117] identified over 300 cellular proteins that bind to the PA protein by liquid chromatography-tandem mass spectrometry (LC-MS/MS) and ~20 % of them are mitochondrial proteins.…”
Section: Involvement Of Pa In Virus and Host Interactionmentioning
confidence: 98%
“…Thus, the MCM is a host factor that regulates the influenza virus genome replication by modulating the interaction between the viral polymerase and the promoter through its contact with PA. Recently, HAX1 protein with anti-apoptotic function has been identified as a new PA-interacting protein [124,125]. This cellular protein specifically interacts with the NLS domain of PA and inhibits PA nuclear accumulation and viral propagation [124].…”
Section: Involvement Of Pa In Virus and Host Interactionmentioning
confidence: 99%
See 2 more Smart Citations